Neurotherapeutic Effect of Inula britannica var. Chinensis against H2O2-Induced Oxidative Stress and Mitochondrial Dysfunction in Cortical Neurons - Jin Young Hong; Hyunseong Kim; Junseon Lee; Wan-Jin Jeon; Seung Ho Baek; In-Hyuk Ha (MDPI AG, 2021)
Inula britannica var. chinensis (IBC) has been used as a traditional medicinal herb to treat inflammatory diseases. Although its anti-inflammatory and anti-oxidative effects have been reported, whether IBC exerts neuroprotective effects and the related mechanisms in cortical neurons remain unknown. In this study, we investigated the effects of different concentrations of IBC extract (5, 10, and 20 µg/mL) on cortical neurons using a hydrogen peroxide (H2O2)-induced injury model. Our results demonstrate that IBC can effectively enhance neuronal viability under in vitro-modeled reaction oxygen species (ROS)-generating conditions by inhibiting mitochondrial ROS production and increasing adenosine triphosphate level in H2O2-treated neurons. Additionally, we confirmed that neuronal death was attenuated by improving the mitochondrial membrane potential status and regulating the expression of cytochrome c, a protein related to cell death. Furthermore, IBC increased the expression of brain-derived neurotrophic factor and nerve growth factor. Furthermore, IBC inhibited the loss and induced the production of synaptophysin, a major synaptic vesicle protein. This study is the first to demonstrate that IBC exerts its neuroprotective effect by reducing mitochondria-associated oxidative stress and improving mitochondrial dysfunction.